Managing Chronic Rhinosinusitis with Nasal Polyps in the Elderly: Challenges and Solutions - Merrill T; Kanaan A (Clinical Interventions in Aging, 2022)
Tyler Merrill, Alissa Kanaan University of Arkansas for Medical Sciences, Department of Otolaryngology – Head and Neck Surgery, Little Rock, AR, USACorrespondence: Tyler Merrill, University of Arkansas for Medical Sciences, Department of Otolaryngology – Head and Neck Surgery, 4301 W. Markham Street, #543, Little Rock, AR, 72205, USA, Tel +1 (501) 686 5140 ; +1 (330) 285 1750, Fax +1 (501) 686 8029, Email tmerrill@uams.eduAbstract: The proportion of the population over 65 years old continues to grow. Chronic rhinosinusitis is common in this population and causes a reduction in quality of life and an increase in health care utilization. Diagnosis of chronic rhinosinusitis with nasal polyps follows the same principles for elderly patients as in the general population, but the elderly population presents some diagnostic challenges worth considering. Presbynasalis, the anatomic and functional changes of the nose and paranasal sinuses associated with aging must be accounted for when caring for these patients. In addition, polypharmacy and other medical issues that can cause similar symptoms must be considered. Medical therapy is generally similar to the general population but with additional concerns given the propensity for geriatric patients to be on multiple medications and to suffer from multiple medical issues. Sinus surgery should be considered following the same indications as in the general population. While some authors have found higher complication rates in endoscopic sinus surgery, others have found higher rates of success. As always, the risks of surgery must be considered with the possible benefits on a patient-to-patient basis.Keywords: sinusitis, nasal polyps, CRSwNP